Early lung disease in infants and preschool children with cystic fibrosis: What have we learned and what should we do about it? - Ranganathan, S.; Hall, Graham; Sly, P.; Stick, S.; Douglas, T. (American Thoracic Society, 2017)
© Copyright 2017 by the American Thoracic Society. The past decade has seen significant advances in understanding of the pathogenesis and progression of lung disease in cystic fibrosis (CF). Pulmonary inflammation, infection, and structural lung damage manifest very early in life and are prevalent among preschool children and infants, often in the absence of symptoms or signs. Early childhood represents a pivotal period amenable to intervention strategies that could delay or prevent the onset of lung damage and alter the longer-term clinical trajectory for individuals with CF. This review summarizes what we have learned about early lung disease in children with CF and discusses the implications for future clinical practice and research.